(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
ischemic type disorders of cerebral circulation (ITDCC) are one of the most common pathologies worldwide. According to the World Health Organization (WHO), ITDCC has been identified in 10-15% of the population, ranking it second in mortality after acute myocardial infarction. It is possible to cite stenosis (Takayasu’s disease) and pathological deformities of the carotid arteries as the causes of ITDCC [1,3,6]. To date, stenosis and pathological deformities of the carotid arteries have been detected in 70-80% of cases, causing problems in the course of these diseases with severe complications, as well as in the conduct of treatment and prevention. Numerous pathologies of other organs of the body can be observed as an additive in patients, and this category causes its influence on the results of surgical treatment of patients, as well as the emergence of serious complications